Development of a cohort multiple randomized clinical trial to test an integrated system of sensors and multimedia monitors technology, for stroke rehabilitation: the ROOMMATE study protocol - Doronzio, Stefano; Jansen-Kosterink, Stephanie; Tesi, Margherita; Castagnoli, Chiara; Pedrini, Chiara; Ciapetti, Tommaso; De Marco, Mario; Piazzini, Michele; Giacani, Julieta; Ciobanu, Ileana; Berteanu, Mihai; Fiorini, Laura; et al. (Frontiers in Neurology, 2025)
BackgroundStroke remains a leading cause of disability globally, creating significant challenges for healthcare systems. Early intensive rehabilitation is recommended (NICE2023) for functional recovery; but standard therapy may not cover all patients’ needs. Stroke survivors should continue active task practice outside of scheduled therapy sessions (self-directed, or semi-supervised by family and caregivers), possibly by sustainable technological solutions. However, most technology-based ecosystems are not designed for healthcare. To test a digital stroke rehab ecosystem Randomized Clinical Trials (RCTs) are the gold standard, but present ethical and logistical challenges, particularly in blinding and participant adherence. This study protocol (ClinicalTrials.gov; NCT06728020; March 21 st, 2025) employs a cohort multiple RCT (cmRCT) innovative design, suitable for comparing usual care to interventions in studies with multiple interventions: cmRCT enrols a large observational cohort, allowing random selection of participants for individual trials rather than random allocation for all subjects, alongside a patient-centered approach to information and consent.MethodsA certified device including a multimedia monitor with virtual reality cognitive and motor rehabilitation exercises (VRRS) will be enriched with educational videos and rehabilitation contents, developed by co-creation involving stroke patients, caregivers and rehabilitation professionals (VRRS1). A dynamic cohort of post-acute stroke inpatients will then be prospectively enrolled in a cmRCT: first, the VRRS1 will be randomly proposed to and tested with 70 subjects, while 70 other eligible patients will be randomized to Usual Care (UC) - controls (ROOMMATE 1st); then, the VRRS1, integrated with a set of inertial sensors (BMR4ROOMMATE) (VRRS2), will be tested in a pilot RCT on 30 patients (while 30 other eligible patients will be randomized as controls - ROOMMATE 2nd). The primary outcome will be the Modified Barthel Index, while secondary outcomes will include measures of motor and cognitive functions, as well as feasibility, usability, and device wearability.ConclusionBy combining sensor-based assessment, expert coaching on digital literacy, and the active involvement of patients, caregivers, and healthcare professionals ROOMMATE aims to co-create an innovative digital ecosystem for Stroke rehabilitation. By rigorously verifying its impact by a cmRCT, it seeks evidence to enhance stroke recovery beyond usual care.